Cyst-theca relationships of Spiniferites bentorii, S. hyperacanthus, S. ramosus, S. scabratus and molecular phylogenetics of Spiniferites and Tectatodinium (Gonyaulacales, Dinophyceae). Issue 4 (4th July 2021) - Gu, Haifeng; Huo, Kai; Krock, Bernd; Bilien, Gwenael; Pospelova, Vera; Li, Zhen; Carbonell-Moore, Consuelo; Morquecho, Lourdes; Ninčević, Živana; Mertens, Kenneth Neil
ABSTRACT: It is well known that modern resting cysts with morphologies matching those of species of the fossil genus Spiniferites germinate into motile cells of the genus Gonyaulax . Different Spiniferites species have been connected to a single Gonyaulax species, raising the question of whether they are over-classified. Through germination experiments of cysts with the morphological features of four species of Spiniferites, viz. S. bentorii, S. hyperacanthus, S. ramosus and S. scabratus, we established cyst-theca relationships. Cysts with the morphology of S. bentorii gave rise to vegetative, motile cells of Gonyaulax nezaniae sp. nov ., which is characterized by two stout antapical spines. Cysts with S. hyperacanthus and S. ramosus morphologies germinated into Gonyaulax whaseongensis and G. spinifera, respectively. Cysts with S. scabratus morphology lacked a ventral pore and were attributed to Gonyaulax cf. spinifera . Gene sequences for SSU, LSU and/or ITS-5.8S rRNA were obtained from these four species, and from cysts with the morphology of Spiniferites belerius, S. mirabilis, S. lazus, Spiniferites cf. bentorii and Tectatodinium pellitum . The maximum likelihood and Bayesian inference analyses based on LSU and SSU rRNA gene sequences revealed that cysts assignable to Spiniferites formed a polyphyletic group, intermingled with Tectatodinium, Bitectatodinium, Ataxiodinium and Impagidinium, whereas Gonyaulax species appeared as monophyletic. From our results we inferred the phylogenetic positions of S. bentorii, S. mirabilis, S. lazus, S. scabratus, Tectatodinium pellitum and Gonyaulax digitale for the first time, supporting the idea that Spiniferites species are not over-classified and each of them may correspond to different Gonyaulax species.